Processing static and dynamic diagrams: Insights from eye tracking - Lowe, Ric; Boucheix, J. (2012)
Empirical studies of static and dynamic diagrams have traditionally collected outcome data indicating the effectiveness of these depictions with respect to comprehension and learning. Because outcome measures alone provide limited insights as to why diagrams are or are not effective, there has been growing interest in studying how people process these depictions. In some cases, the aim of this research is to develop principled approaches for guiding diagram design while in others it is to devise strategies that could support users. This paper presents a selection of examples from varied content domains illustrating how eye tracking data can be combined with other measures to probe how users interact with diagrams. Descriptions of the systems used in these combinations will be described and the synergies between eye tracking and the other measures explained. The illustrations are selected from studies in which the goals ranged from exploring the effects of cueing to comparing visual and haptic search. These different examples show that approaches used for analysing and interpreting eye tracking data need to be carefully matched to the specific goals of individual studies. We conclude with recommendations for using eye tracking as an adjunct to other approaches for gathering diagram processing data.